2017
DOI: 10.1186/s12909-017-1087-9
|View full text |Cite
|
Sign up to set email alerts
|

Medical student researchers in Colombia and associated factors with publication: a cross-sectional study

Abstract: BackgroundGaps between evidence-based research and clinical-public health practice have been evident for decades. One of the aims of medical student research is to close this gap. Accordingly, evaluating individual and environmental factors that influence participation of medical students in research are needed to understand and identify potential targets for action. This study aims to identify characteristics of medical student researchers in Colombia and the associated factors with scientific publications.Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
24
2
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(43 citation statements)
references
References 30 publications
7
24
2
4
Order By: Relevance
“…The major obstacle found in this research was the heavy load from studies or internships, which corresponds with previous results [4,7]. The most de cient research abilities were research design and statistical analysis, which was also consistent with other studies [24,25]. Students performed relatively better in academic reading and writing, probably because the ve medical schools in this study all provided related compulsory courses.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The major obstacle found in this research was the heavy load from studies or internships, which corresponds with previous results [4,7]. The most de cient research abilities were research design and statistical analysis, which was also consistent with other studies [24,25]. Students performed relatively better in academic reading and writing, probably because the ve medical schools in this study all provided related compulsory courses.…”
Section: Discussionsupporting
confidence: 89%
“…The modern medical education system has been engaging medical students in research for nearly half a century, and students' feedback has been generally positive in the USA [9][10][11]. Research training provides valuable experience for medical students, cultivating their interest in research and allowing them to critically evaluate new research ndings and advanced medical knowledge [13][14][15]. Brancati et al found that career achievement was related to research experience in medical school [16].…”
Section: Discussionmentioning
confidence: 99%
“…For the primary outcome measure, we defined scientific publication output as scholarly publications limited to case reports, reviews or original research papers [20]. Reviews were limited to systematic reviews, meta-analysis, scoping reviews or rapid literature reviews and excluded book reviews.…”
Section: Primary Outcome Measurementioning
confidence: 99%
“…Parts of the survey items were adapted from previously published studies, Khan et al [9], Bonilla-Escobar et al [20], Niwa et al [21] and Bovijn et al [22], with additional items being added to further conceptualise our study objectives and sample characteristics. The questionnaire was pre-piloted prior to data collection to assess its comprehensibility and ease of completion.…”
Section: Pilot Testing and Veracitymentioning
confidence: 99%
“…However, there are still gaps in Latin America when comparing to research university systems from developed countries in terms of the number of publications, the quality of articles published, the outreach of the studies, and funding opportunities (5). Studies in Colombia and Brazil show that medical students consider scientific research as an important issue of their training and the low scientific production is influenced by the lack of inspirational and committed mentors as role models for the beginning of a scientific career (6,7).…”
Section: Introductionmentioning
confidence: 99%